Managing the time issue in GIS - Juhász, Attila (Acta Agraria Kaposváriensis, 2010)
There is no general and comprehensive solution to manage time data – like spatial data – in GIS. The widely known concepts developed to solve special problems. In my paper I review these concepts, the problems of handling the time data and the viewpoints of grouping (application, duration, update, presentation, time-space dominance). I detail the main functions of the spatiotemporal GIS datamodels. Finally I discuss the problems of time issue in my own research theme, the military historical reconstruction.